Application of Folding Architecture in the Design of Modern Music Center in Pekanbaru - Farhah Duratul Adibah; Indra Kuswoyo; Morian Saspriatnadi; Nurrul Helen; Oriana Paramita Dewi; Laili Dwi Annisa (Program Studi Arsitektur, Fakultas Teknik, Universitas Riau, 2026)
The development of modern music activities in Pekanbaru has increased significantly; however, integrated facilities that accommodate music education, practice, production, and performances remain limited. This study aims to explore the application of the folding architecture approach in the design of a Modern Music Center in Pekanbaru. The design process employed the method proposed by Jones (1972), consisting of the stages of ideas, information and analysis, synthesis, evaluation, and optimization. Data were collected through site surveys, documentation, interviews, literature review, and precedent studies. The results indicate that the folding approach generates dynamic and expressive forms and spaces that correspond to the rhythmic and evolving nature of modern music. The Melody Beat concept was translated into architectural form through folded geometries that influenced spatial organization, façade expression, and users' spatial experience. In addition to creating a distinctive visual identity, this approach also has the potential to support spatial flexibility and acoustic quality within the building.